Perbandingan Aktivitas Antidiare Ekstrak Etanol Daun Seledri Dan Biji Pinang Pada Mencit Terinduksi Minyak Jarak - Putri, Sami Mardiah; Yansen, Fatridha; Humaira, Vilma (Jurnal Medisains Kesehatan, 2025)
Diarrhea remains a significant health problem in Indonesia, especially among children. The use of medicinal plants as alternative therapy continues to grow due to their milder side effects compared to synthetic drugs. This study aimed to compare the antidiarrheal activity of ethanol extracts of celery leaves (Apium graveolens L.) and areca nuts (Areca catechu L.) on mice (Mus musculus L.) induced with castor oil. The experiment was conducted in a laboratory using a post-test only control group design involving 27 male mice divided into three groups: control, celery leaf extract (20 mg/kgBW), and areca nut extract (350 mg/kgBW). One Way ANOVA showed significant differences among groups in defecation frequency and diarrhea onset (p < 0.05; p = 0.000). The mean defecation frequency was 16 times in the control group, 13 in the celery extract group, and 8 in the areca extract group. Diarrhea onset occurred at 69.25 minutes, 51.75 minutes, and 37.5 minutes, respectively. The areca nut extract at 350 mg/kgBW was the most effective antidiarrheal agent, reducing defecation frequency and delaying diarrhea onset. This effect is attributed to secondary metabolites such as flavonoids, tannins, saponins, and alkaloids, which which act as natural antidiarrheals